PENGARUH PENGAWASAN KEPALA SEKOLAH DAN KOMPENSASI TERHADAP KINERJA GURU PADA SEKOLAH DASAR SE-KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - Supriadi; Isjoni; Sri Kartikowati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the effect of school principal supervision and compensation on elementary school teachers’ performance in Simpang Kanan, Rokan Hilir. The study used a survey method with correlational techniques involving 115 teachers. Data were collected through questionnaires and documentation and analyzed using SPSS version 20 with product-moment correlation. The results showed that principal supervision and compensation had a positive but not significant effect on teachers’ performance individually. However, simultaneously, principal supervision and compensation had a significant positive effect on teachers’ performance (Fcount = 19.091 > Ftable = 3.08, p < 0.05).